Estimating the Amount and Source of Night-time Light - Horvath, Anna (Trinity College Dublin, School of Physics, 2025)
The global share of electricity consumption related to lighting reduced to 12% in 2024 from 18% recorded in 2005, but artificial light output increased from 135 petalumen-hours (Plmh) to 240 Plmh between 2005 and 2024. This increase in light output has been investigated using satellite imagery, which captures urban activity from various illumination sources such as street lighting, residential lighting, and commercial lighting, collectively referred to as Artificial Light at Night (ALAN). The growth in ALAN has not been fully understood whether it is due to increased street lighting, or other light sources. However, previous studies lacked investigation of the combined importance of nighttime light sources stemming from street lighting, residential lighting, and commercial lighting together, and were instead focused on only one of them. Here, we show using data from the Sustainable Development Goals Science Satellite 1 (SDGSAT-1) with a spatial resolution of 10 m alongside International Space Station imagery and the Visible Infrared Imaging Radiometer Suite (VIIRS) that there is more than 50 GWh of electricity use in Dublin resulting in 11,500 tonnes of CO₂ emissions annually related to public and private lighting. We show that the largest light contribution comes from residential areas and from areas of high commercial activity, which correlate well with electricity use. Thus, results demonstrate that private lighting is a major contributor to electricity use and to related CO₂ emissions. The main subject of environmental policy has so far been focused on public lighting, which is important but does not address the problem around the high energy demand related to lighting. Hence, environmental policy must also include private lighting measures. The project describes spatial and temporal variation of light output in different land use areas in Dublin to investigate which are the largest contributors that should be considered in energy efficiency policies. Private lighting from commercial and residential areas is characterised by poorly directed and shielded lights. Sharpened SDGSAT imagery shows that such lights tend to emit light upwards and sideways, thereby contributing to energy lost to space and to skyglow above cities. The project also contains recommendations to reduce the energy demand of both private and public lighting.
APPROVED
This report involves a time-resolved study of light pollution and energy use of the Dublin area using satellite data with 10m/pixel resolution. The research shows that there is a significant contribution of non-public light contribution to the overall light and energy burden.
Keywords: NATURAL SCIENCES::Earth sciences::Other earth sciences; Smart & Sustainable Planet; Light Pollution; Public Policy; energy waste; Environment and housing; Health